Corn growth on gold-mine tailings inoculated with nitrogen-fixing and phosphate-solubilizing bacteria - Sunarya, Yaya -; Priyadi, Rudi; Arifin, Mahfud; Hindersah, Reginawanti (Jurnal AGRO, 2024)
Gold-mine tailings, challenging environment for plant growth, was our study focus. Introducing nitrogen-fixing bacteria (NFB) and phosphate-solubilizing bacteria (PSB) provides nutrients and phytohormones for plant growth. A pot experiment was designed to assess the corn growth on tailing inoculated with NFB and PSB. The research, conducted in a completely randomized block design, was replicated seven times; the treatments were : without inoculation (control), single inoculation of Azo-7.2, single inoculation of BPF-9, a mixture of Azo-7.2 and BPF-9. The results revealed that inoculation of NFB and PSB significantly increased plant height, stem diameter, leaf number, and P-uptake but did not affect leaf area, chlorophyll content, root length, S/R ratio, N-uptake, and plant biomass, and NFB and PSB count in the rhizosphere. Single inoculants of BPF-9 and mixed inoculants increased plant height by 1.2% to 7%, stem diameter, leaves number, and S/R ratio; only mixed inoculation increased N-uptake, however, Azo-7.2 potential to enhance leaf area, chlorophyll content, and corn biomass. The population of NFB and PSB in the rhizosphere of all treated and control plants was slightly lower than the initial population. The research, in particular, verified that the corn growth on tailings inoculated with NFB and PSB was better than that of uninoculated. ABSTRAK Tailing tambang emas yang merupakan tantangan untuk pertumbuhan tanaman, menjadi fokus penelitian ini. Inokulasi bakteri pengikat nitrogen (BPN) dan bakteri pelarut fosfat (BPF) menyediakan nutrisi dan fitohormon yang penting untuk pertumbuhan tanaman. Percobaan pot dirancang untuk mengevaluasi kinerja pertumbuhan jagung (Zea mays L.) pada tailing yang diinokulasi dengan BPN dan BPF. Penelitian dilakukan dengan rancangan acak kelompok yang diulang sebanyak tujuh kali; perlakuan percobaan adalah tanpa inokulasi (kontrol) dan dengan inokulasi tunggal BPN Azo-7.2 dan BPF-9 serta campuran Azo-7.2 dan BPF-9. Hasil penelitian menunjukkan bahwa inokulasi BPN dan BPF dengan nyata meningkatkan tinggi tanaman, diameter batang, dan jumlah daun tetapi tidak mempengaruhi luas daun, kandungan klorofil, panjang akar, biomassa tanaman, serta jumlah BPN dan BPF di rizosfer. Inokulan tunggal BPF-9 dan inokulan campuran campuran meningkatkan tinggi tanaman 1,2% sampai 7%, diameter batang, jumlah daun, dan rasio S/R secara signifikan. Namun Azo-7.2 berpotensi untuk meningkatkan luas daun, kandungan klorofil, dan biomassa jagung. Populasi BPN dan BPF di rizosfer seluruh tanaman yang diberi perlakuan dan kontrol sedikit lebih rendah dibandingkan populasi awal sebelum percobaan. Penelitian ini, secara khusus, memastikan bahwa performansi pertumbuhan jagung pada tailing yang diinokulasi dengan BPN dan BPF lebih baik dibandingkan dengan tanaman di tailing tanpa inokulasi.